MODEL BENEISH M-SCORE UNTUK MENDETEKSI KECURANGAN PADA PERUSAHAAN PERBANKAN DI INDONESIA - marfuah Marfuah (Optimum: Jurnal Ekonomi dan Pembangunan, 2018)
ABSTRACTThe objectives of this research areÂ  (1) to know the ability of Beneish M-Score in detecting the occurrence of fraud in banking companies in Indonesia and (2) to test whether Beneish M-Score in the fraud banking samples according to Supreme Court decision is greater compared to non-fraud banking samples. Based on the discriminant analysis, the significant variables that can be used to detect the occurrence of fraud are AQI, SGI and SGAI. However, only the SGAI variable alone has a significant influence on the dependent variable so that the discriminant equation function Z = -4.923 + 4.958SGAI is formed. The classification results show the percentage accuracy Beneish M-Score in detecting the occurrence of fraud is equal to 75.5%. Meanwhile, based on the Independent sample T-test proved that the Beneish M-Score ratio in the banking sample of corruption cases is significantly greater than in the banking sample that did not happen corruption cases. The results of this study prove that if Beneish M-Score able to detect well the occurrence of fraud in banking companies, then Beneish M-Score on the sample of banking that there is fraud or corruption is greater than the sample banking that does not happen fraud or corruption.Â Â